'Give us bread, but give us roses': Gender and labour in the digital economy. (1st June 2014) - Shade, Leslie Regan
This article provides an overview of contemporary scholarship in information and communication studies on labour and gender in the digital economy. It also discusses recent feminist perspectives on social media attributes around labour, including the paucity of women working in the social media industry, and the gendered dimension of young unpaid interns. Control of the means of communication and production is a dominant and perturbing theme throughout much of the research and activism. The article concludes with suggested venues of further research for students and scholars in order to energize pedagogy and practice in critical communication studies.